Dye‐Sensitized Solar Cells: Resonant Multiple Light Scattering for Enhanced Photon Harvesting in Dye‐Sensitized Solar Cells (Adv. Mater. 30/2014). (August 2014) - Kim, Jihun; Lee, Horim; Kim, Dong Young; Seo, Yongsok
<x xml:space="preserve">Abstract</x> On page 5192, Y. Seo and co‐workers describe a new benchmark set for dye‐sensitized solar‐cell performance using a novel dye. The fabrication of a very efficient resonant lightscattering device with a high photocurrent and good stability is described. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>